Biaxially Morphing Droplet Shape by an Active Surface. Issue 2 (26th August 2020) - Wang, Ding; Liu, Yingzhi; Sridhar, Sreepathy; Li, Yifan; McHale, Glen; Lu, Haibao; Yu, Ziyi; Wang, Steven; Xu, Ben Bin
Abstract: Drop morphology can be manipulated by designing localized solid/liquid interactions to create a favorable interfacial energy equilibrium. A topographical surface with hierarchical roughness can be harnessed to generate complex drop morphologies, enhance uniaxial and anisotropic spreading, in a designable fashion. Here, using an active surface is proposed with a responsive roughness (wrinkle patterns) under uniaxial compression/stretching, to morph droplet shape biaxially in a continuous and reversible manner. The keys to achieve biaxial drop shaping are the in‐plane confinement from lattice hole patterns and the programmable formation of roughness, to pin and guide contact line movement in both in plane directions. The complex interplay between wetting and the patterns is elucidated by both experiments and numerical analysis. The results enrich the current understanding of shaping droplets by managing the contact line pinning/movement on an engineered elastic substrate, and providing insights for emerging applications in the areas such as droplet emicrofluidics, liquid robotics, ink‐jet printing, 3D printing and healthcare. Abstract : The distribution of surface capillary upon an elastic surface can be reversibly adjusted with the patterned lattice holes and initiation of wrinkles. Such switchable surface wetting enables the pinning and guided moving of contact line for the droplet on surface, yield a biaxially morphing of droplet shape in a controllable manner.